The Organization of Trade in Nemunas from the Riverhead ports of the Radziwiłł and Sapieha families in the 1760s and 1770s - Sakalauskas, Darius; Poška, Aivaras (Lietuvos istorijos studijos, 2020)
This study concerns the transportation of goods and raw materials through the Nemunas River to the Baltic Sea ports in the second half of the 18th century. The main goal of this paper is to analyse how two different methods of goods transportation (shipment of goods by river vessels and by timber rafts) were organized and to determine how their economic models functioned in practice. This research relies on the data of Income-Expenditure registers of timber rafting from Radziwiłł (Świerżeń Nowy) and goods transportation from Sapieha family (Ruzhany and Derechin) estates in current-day Belarus. The analysis showed that the Sapieha family’s highest share of revenue derived mostly from the exportation of grown raw materials, mostly rye. Salt, wine, beer, various types of metal alloys, etc. were bought in exchange. Part of the revenue was used to cover debts, thus the generated income of the voyage did not reach the treasury of the Sapieha family. The analysis of timber-rafting income-expenditure showed that the timber was drifted to the town of Rusnė, near the Nemunas river delta, or to the city of Königsberg. The sources failed to show the full extent of timber trade generated revenue due to the specifics of its trade, however, the analysis showed that the biggest part of expenditures (about 90–95 percent) went on the hiring of employees and on timber preparation and it’s transportation to the river ports. This article also uncovers the different aspects of how these different kinds of trade voyages were organized and how the river trade-related infrastructure operated that supplements our understanding of the Nemunas river role in the economy of Grand Duchy of Lithuania in the second half of 18th century.